2015
DOI: 10.1111/ijjs.12039
|View full text |Cite
|
Sign up to set email alerts
|

Combining Egalitarian Working Lives with Traditional Attitudes: Gender Role Attitudes in Taiwan, Japan, and Korea

Abstract: In a simple theoretical framework, egalitarian gender role attitudes emerge as more and more women participate in the labor market. Most advanced Western nations enjoy relatively gender-egalitarian working environments, and consequently more egalitarian gender attitudes than their East Asian counterparts. Women in East Asian societies, on the other hand, are said to support both the conditions resulting in stagnant female labor-force participation and traditional attitudes toward gender roles. In Taiwan, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In principle, gender roles consist of four dimensions: work (i.e., income earning) versus family (i.e., housework and childcare) roles for each of the two male and female gender groups. The distinction is necessary, because people's attitudes are not consistently symmetrical between the roles of women and men and between the areas of these roles, as widely observed across many societies and often referred to as a stalled gender revolution (England 2010;Knight and Brinton 2017;Lee 2016;Raymo et al 2015;Takeuchi and Tsutsui 2016). For example, strong support for women's gainful employment outside the home may accompany strong support for men's family roles but not necessarily pair with strong support for men being exempted from provider roles.…”
Section: Dimensions Of Gender Roles and Typology Of Gender Role Normsmentioning
confidence: 99%
“…In principle, gender roles consist of four dimensions: work (i.e., income earning) versus family (i.e., housework and childcare) roles for each of the two male and female gender groups. The distinction is necessary, because people's attitudes are not consistently symmetrical between the roles of women and men and between the areas of these roles, as widely observed across many societies and often referred to as a stalled gender revolution (England 2010;Knight and Brinton 2017;Lee 2016;Raymo et al 2015;Takeuchi and Tsutsui 2016). For example, strong support for women's gainful employment outside the home may accompany strong support for men's family roles but not necessarily pair with strong support for men being exempted from provider roles.…”
Section: Dimensions Of Gender Roles and Typology Of Gender Role Normsmentioning
confidence: 99%
“…Furthermore, the gender role attitudes of human beings can be altered due to the education level of the parents, the mother's work status, family atmosphere, siblings and friends, teachers, textbooks, and the mass media 17 . Particularly, if the education level of mothers is getting higher and if the mother works, children tend to have more egalitarian attitudes 17–19 . In this study, it has been shown that the education level increased in the first, second, and third generations.…”
Section: Discussionmentioning
confidence: 65%
“…In the past several decades, Taiwan has seen increases in both female labor force participation and female educational attainment, and the society is Taking gender ideologies seriously moving away from traditional gender ideologies (Ho et al, 2010). Compared with other East Asian countries, Taiwanese people have more egalitarian gender ideologies (Lee, 2017), but Taiwanese women still experience imbalances between family duties and work (Takeuchi and Tsutsui, 2016). Hofstede (1984) defined Taiwan as a low-to-medium masculine society, and an updated data published in 2015 still found that Taiwan is a low-to-medium masculine society (Hofstede, 2015).…”
Section: Research Design and Research Contextmentioning
confidence: 99%